The Influence of Self Awareness Towards Speaking Ability of The Tenth Grader of SMKN 1 Ampana Tete - Umaira, Siti; Rofiqoh, Rofiqoh; Mashuri, Mashuri (Universitas Sintuwu Maroso, 2025)
Abstract: The objectives of this research are to find out the influence of self-awareness towards the speaking ability of tenth- grade students and to find out the student’s ability in speaking English. The method of this research was quantitative research with a correlation design. The population of this research was the tenth-grade students of SMK Negeri 1 Ampana Tete. The total number of the students was 78 students. There were two classes, involved one class consisted of 30 students. The sample was selected by using a purposive sampling technique. The data collection was began with the speaking test. Then, the students were asked to answer a questionnaire. After obtaining the data, the researcher analyzed the data using a Pearson Product Moment correlation method that examined the correlation between the two variables. The findings in this research show from 30 respondents there are; 80% of the students had high Self- awareness, and 17% of the students had low Self-awareness. The result of the mean score of the speaking student’s score is 43. It means that students had a poor ability to speak English. The result of the correlation between Self-awareness and speaking ability is very low, it means that there is almost no influence between self-awareness and speaking ability of the tenth grade students of SMK Negeri 1 Ampana Tete.